Pharmacodynamic effects of C-domain-specific ACE inhibitors on the renin-angiotensin system in myocardial infarcted rats. (December 2015) - Sharp, Sarah; Poglitsch, Marko; Zilla, Peter; Davies, Neil H; Sturrock, Edward D
Introduction: The renin-angiotensin system (RAS) is a dynamic network that plays a critical role in blood pressure regulation and fluid and electrolyte homeostasis. Modulators of the RAS, such as angiotensin-converting enzyme (ACE) inhibitors, are widely used to treat hypertension, heart failure and myocardial infarction. Methods: The effect of ACE inhibitors (lisinopril and C-domain-selective LisW-S) on the constituent peptides of the RAS following myocardial infarction was examined in rats. Ten angiotensin peptides were analysed using a sensitive LC-MS/MS-based assay to examine both the circulating and equilibrium levels of these peptides. Results: Administration of lisinopril or LisW-S caused a significant decrease in Ang 1–8/Ang 1–10 ratios as determined by circulating and equilibrium peptide level analysis. Furthermore, Ang 1–7 levels were elevated by both ACE inhibitors, but only lisinopril decreased the Ang 1–5/Ang 1–7 ratio. This indicates LisW-S C-domain specificity as Ang 1–5 is generated by hydrolysis of Ang 1–7 by the N-domain. Further corroboration of LisW-S C-domain specificity is that only lisinopril increased the circulating levels of the N-domain ACE substrate Ac-SDKP. Conclusion: LisW-S is able to effectively block ACE in vivo by C-domain-selective inhibition. The LC-MS/MS-based assay allows the evaluation of the pharmacologic impact of RAS inhibitors in different pathophysiological conditions.